3x+2(x-1)=9x=4
We move all terms to the left:
3x+2(x-1)-(9x)=0
We add all the numbers together, and all the variables
-6x+2(x-1)=0
We multiply parentheses
-6x+2x-2=0
We add all the numbers together, and all the variables
-4x-2=0
We move all terms containing x to the left, all other terms to the right
-4x=2
x=2/-4
x=-1/2
yes because if you look you can see a pattern of 4 if we divide 2 AND 8 WE GET 4 AND SO.
Answer:
V≈3619.11cm³
Step-by-step explanation:
The correct product of (6x - 2)(6 x + 2) is 36x^2 - 4
<h3>How to determine the product?</h3>
The expression is given as:
(6x - 2)(6 x + 2).
The above expression is a difference of two squares.
And this is represented as
(a - b)(a + b)= a^2 - b^2
So, we have
(6x - 2)(6 x + 2) = (6x)^2 - 2^2
Evaluate
(6x - 2)(6 x + 2) = 36x^2 - 4
Hence, the correct product of (6x - 2)(6 x + 2) is 36x^2 - 4
Read more about difference of two squares at:
brainly.com/question/3189867
#SPJ1
<u>Complete question</u>
What is the product?
(6x - 2)(6 x + 2).
Answer:
length is 78
Step-by-step explanation:
Perimeter of rectangle is P = 2 (l +w)
278 = 2(l + 61)
l = 78